Degradation of tetracycline by photo-Fenton process - Solar irradiation and matrix effects - Bautitz, Ivonete Rossi; Nogueira, Raquel Fernandes Pupo [UNESP] (Elsevier B.V., 2007)
The degradation of the antibiotic tetracycline (TC) by the photo-Fenton process was evaluated under black-light and solar irradiation. The influences of iron source (Fe(NO3)(3) or ferrioxalate), hydrogen peroxide and matrix (pure water, surface water and a sewage treatment plant effluent-STP) were evaluated. Under black-light irradiation, TC degradation was favored in the presence of Fe(NO3)(3), achieving total degradation after 1 min irradiation, while under solar light the use of ferrioxalate favors the degradation. Nevertheless, no significant difference in total organic carbon removal was observed between these two iron sources, achieving a residual concentration of around 5 mg L-1 under black-light and 2 mg L-1 under solar light irradiation. No decrease of the degradation efficiency relative to pure water was observed when TC was irradiated in a sample of surface water, under either black-light or solar irradiation. However, lower efficiency was obtained under black-light when TC was present in a sample of STP effluent, indicating the interference of the constituents of this sample on the overall efficiency of the process. on the other hand, under solar irradiation in the presence of ferrioxalate, no influence of the matrix was observed, even in the sample of STP effluent, achieving total degradation of TC in 1.5 min. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: advanced oxidation process; sewage treatment plant; antibiotic; ferrioxalate